2006
DOI: 10.1002/bem.20210
|View full text |Cite
|
Sign up to set email alerts
|

14.6 mT ELF magnetic field exposure yields no DNA breaks in model systemSalmonella, but provides evidence of heat stress protection

Abstract: In this study, we demonstrate that common extremely low frequency magnetic field (MF) exposure does not cause DNA breaks in this Salmonella test system. The data does, however, provide evidence that MF exposure induces protection from heat stress. Bacterial cultures were exposed to MF (14.6 mT 60 Hz field, cycled 5 min on, 10 min off for 4 h) and a temperature-matched control. Double- and single-stranded DNA breaks were assayed using a recombination event counter. After MF or control exposure they were grown o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…Luceri et al (2005) reported that extremely-low frequency MF (1, 10 and 100 mT, 50 Hz, 18 h) do not induce DNA damage or affect gene expression in S. cerevisiae. Williams et al (2006) observed that 60 Hz, 14.6 mT MF cycled (5 min on, 10 min off; 4 h) does not cause DNA breaks. They used the model organism Salmonella enterica defectives in the recA recombination repair mechanism, required to repair single or double DNA strand breaks in the strains used by these authors.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Luceri et al (2005) reported that extremely-low frequency MF (1, 10 and 100 mT, 50 Hz, 18 h) do not induce DNA damage or affect gene expression in S. cerevisiae. Williams et al (2006) observed that 60 Hz, 14.6 mT MF cycled (5 min on, 10 min off; 4 h) does not cause DNA breaks. They used the model organism Salmonella enterica defectives in the recA recombination repair mechanism, required to repair single or double DNA strand breaks in the strains used by these authors.…”
Section: Discussionmentioning
confidence: 89%
“…Genotoxic effects of EMF may occur directly by damage to DNA and DNA repair mechanisms (Ivancsits et al 2002). Controversial results, about the induction of DNA strand breaks or the completely absence of such effects, have been published at different EMF intensity levels (Ivancsits et al 2003, Lai and Singh 2004, Scarfi et al 2005, McNamee et al 2005, Wolf et al 2005, Villarini et al 2006, Williams et al 2006, Ruiz-Gó mez and Martínez-Morillo 2009). The primary MF interaction mechanisms may to involve the Radical Pair Mechanism (RPM) in which low level MF drive pairs of radicals from the singlet to the triplet spin state.…”
Section: Introductionmentioning
confidence: 99%
“…However, since the pulsed magnetic field is not found in nature, DNA has no protective mechanism from it. Probably, that is why the static magnetic field has little effect on DNA and the cell in vivo whereas the pulsated magnetic field affects DNA and the cell radically [320][321][322]330]. According to the same logic we can suggest that periodic long-term gravitational pulsations (lunar tides), as a common phenomenon on Earth, have a protective mechanism against DNA damage (corresponding DNA repair mechanism) whereas static gravitation is uncommon for living organisms on Earth.…”
Section: Triplexmentioning
confidence: 99%
“…Therefore, usually, a low frequency electromagnetic or a low frequency magnetic field (alone or in combination with other factors) can affect DNA; however, some scientists disagree with this opinion [322,323].…”
Section: Triplexmentioning
confidence: 99%
“…Many studies on extremely low frequency (ELF)-MF have showed that exposure to these fields can affect biological functions such as RNA transcription, cell viability, cell proliferation although it is unknown which molecular mechanisms are involved (Babincova et al 2000;Ventura et al 2005;Williams et al 2006;Kroupova et al 2007;Novak et al 2007;Cellini et al 2008). Still it is not still clear whether ELF-MF exposure can represent a stress factor for the cells.…”
mentioning
confidence: 99%